The regional differences in prevalence, medical expenditures and risk factors for injury in Taiwanese teenagers - Lin Yu-Hsuan; Hsu Chih-Cheng; Shih Shu-Fang; Chang Hsing-Yi; Chen Huei-Yang; Shih Yaw-Tang (BMC, 2006)
Abstract Background Injury is the leading cause of death in teenagers worldwide. In Taiwan, people in mountainous areas have a 4 to 8 years shorter life span than the general population. Injury among teenagers is likely a major cause. The objective of this study was to investigate the regional differences in the prevalence, the risk factors, and the medical expenditures for injury among Taiwanese teenagers. Method An equal probability national sample was used. In addition, representative samples from mountainous areas and offshore islands were used. Only those who aged between 12 and 21 years, and signed the consent form permitting us to link their National Health Insurance (NHI) claim data were included in the analysis. Injury-related visits and expenditures in outpatient services were extracted from the NHI data. Logistic regression was used to examine the factors associated with injury. For those who had injury related outpatient visits, mixed model was used to examine the factors associated with medical expenditures accounting for multiple visits by the same individual. Results The prevalence of nonfatal injury was around 30% of teenagers in Taiwan. It was 10% higher in mountainous areas. Factors associated with injury were those who lived in mountainous areas (adjusted odds ratio [OR]: 1.7; 95%; confidence interval [CI]: 1.3-2.3), males (OR: 1.3; 95%; CI: 1.1-1.6), older teens (18-21 years old), and those with risk behavior were positively associated with injury. These factors were also associated with the number of injury-related outpatient visits. However, teenagers in mountainous areas did not spend more on medical care than those who lived in metropolitan Taiwan. Conclusion Around 30% of the teenagers were injured in a year, not including the dead. Each of the injured spent at least 851.4NTD (~27USD) for outpatient visits. The scope of the problem was not trivial. Hazardous environments and high-risk behaviors were the universal causes. In remote areas, lack of medical resources was another possibility. Empowering local people to design prevention programs according to their needs is recommended.